1999
DOI: 10.1007/s005920050150
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and identification of risk factors for type 2 diabetes mellitus and impaired glucose tolerance in Kayseri, central Anatolia, Turkey

Abstract: Type 2 diabetes mellitus is a chronic disease which causes neurologic, cardiac, vascular, ocular and renal complications. The present study documented the prevalence of diabetes and associated risk factors in 1774 adults who were older than 30 years. An oral glucose tolerance test (OGTT) was conducted according to the World Health Organization (WHO) criteria. Of the 1452 subjects, 58 (4%) had diagnosed diabetes, 41 (2.9%) undiagnosed diabetes and 130 (9%) had impaired glucose tolerance. The total glucose intol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
2
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 13 publications
2
14
2
3
Order By: Relevance
“…Gö kçel et al (13) and King et al (10) also reported a greater prevalence of diabetes in men. In another study on the Turkish population, diabetes prevalence was reported to be nearly equal in men and women (11). In the current study, we found a greater prevalence of diabetes in men; however, the difference was not statistically significant.…”
Section: Diagnostic Criteriacontrasting
confidence: 86%
See 1 more Smart Citation
“…Gö kçel et al (13) and King et al (10) also reported a greater prevalence of diabetes in men. In another study on the Turkish population, diabetes prevalence was reported to be nearly equal in men and women (11). In the current study, we found a greater prevalence of diabetes in men; however, the difference was not statistically significant.…”
Section: Diagnostic Criteriacontrasting
confidence: 86%
“…Many studies report age (10,11,13,17) and sex (13) to be risk factors for diabetes. Hypertension was reported to be a risk factor (10,13), as well as family history of diabetes (13,16,17) and obesity (10,13,14,17).…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…In Croatia, diabetes prevalence has been estimated according to data from questionnaires completed by diabetes centers [4]. However, as these were not survey data, the estimates of diabetes prevalence in Croatia as reported in the International Diabetes Federation (IDF) atlas [5,6] have been made by extrapolating data from similar populations [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Genel olarak bakıldığında 1993-1998 yıl-ları arasındaki diyabet prevelansı, çalışılan bölge-lerde %6-7 arasında değişmekte olduğu anlaşılma ktadır. 10,15,16,17,18,19,20 Eskişehir Çifteler kırsal alanında 2000'de 20 yaş ve üzeri kişilerde yapılan bir çalış-mada DM prevalansı %11,0 olarak saptanmıştır.…”
Section: Discussionunclassified